Disparos: ensaios sobre fotografia de guerra - Loconte, Lucas de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Once the choices set involved in the selection of compositional techniques of a photography is mediated by ideological universes, this final project aims to analyze the photographic coverage of the World War II presented in the brazilian publication Revista da Semana during the period in which Brazil was part of the conflict (1942 to 1945). We study the different composition techniques used and the different effects of meaning articulated by these techniques. Thus, our goal is to see how the repetitions are articulated and the translations of meaning in photojournalistic composition from its narrative structure, that is, their way of coded organization. For this, we used the analysis methodology proposed by Umberto Eco on the rhetoric of the image, involving the five levels of photography decomposition (ie iconic levels, iconographic, tropological, topic and enthymematic). We will analyze these images from the perspective of the effects of meaning that the composition techniques to engender glimpse which were woven meanings to this event in that specific space, and which were mediated discourses of Brazilian participation in the conflict

Uma vez que o conjunto de escolhas envolvido na seleção das técnicas composicionais de uma fotografia é mediado por universos ideológicos, o presente trabalho tem como objetivo analisar a cobertura fotográfica da Segunda Guerra Mundial realizada pela Revista da Semana durante o período em que o Brasil fez parte do conflito (1942 a 1945). Estudaremos as diferentes técnicas de composição utilizadas, bem como os diferentes efeitos de sentido articulados por essas técnicas. Com isso, o nosso objetivo é verificar como são articuladas as repetições e as translações de significado na composição fotojornalística a partir de sua estrutura narrativa, ou seja, de sua forma de organização codificada. Para isso, serão utilizadas como metodologia de análise as propostas de Umberto Eco sobre a retórica da imagem, envolvendo os cinco níveis de decomposição da fotografia (a saber, níveis icônico, iconográfico, tropológico, tópico e entimemático). Nós iremos analisar essas imagens sob a perspectiva dos efeitos de sentido que as técnicas de composição engendram para entrever quais foram as significações urdidas a esse acontecimento nesse espaço específico, bem como quais foram os discursos mediados acerca da participação brasileira no conflito
Keywords: Fotografia; Jornalismo; Guerra Mundial - 1939-1945; História; Fotojornalismo; Photography